Pembelajaran Daring Interaktif, Bermakna dan Menarik sebagai Upaya Optimalisasi Proses Pembelajaran masa Pandemi Covid-19 - Irma Savitri Sadikin; Sri Lestari; Safi Aini (Jurnal Pengabdian Pada Masyarakat, 2020)
INTERACTIVE, MEANINGFUL AND ATTRACTIVE ONLINE LEARNING AS AN EFFORT TO OPTIMIZE THE LEARNING PROCESS AMID COVID-19 PANDEMIC. The education policy of the Indonesian government is that temporary online learning has been conducted at almost all levels of education to prevent the spread of the COVID-19 virus. This means that all Indonesian students need to study online. In relation to this, educators must be able to provide engaging, interactive, and productive online learning. This article aims to illustrate the program which promotes the mastery of the relevant online learning that can be applied to students by Elementary school teachers. Mentoring offered by the community service team (PKM) as trainers is the strategy used in community service, which is carried out in three stages: planning, implementing and reflection. The outcome of this service is that English teachers at Perguruan Cikini Elementary School have a variety of online interactive learning. It is also expected that some learning applications can help teachers develop engaging and pleasant online learning experiences so that students can achieve the required learning competence.